Process Development of Mozzarella Farm Cheese from Buffalo Milk - Pandolsook, Sawanya; Tungjaroenchai, Wanna (Journal of Food Health and Bioenvironmental Science, 2023)
The objective of this research was to improve and develop the process of mozzarella cheese manufacturing from buffalo whole milk. Qualities of buffalo raw milk and manufacturing conditions were studied and included curd cutting time (0-75 min), cooking temperature (43, 45 or 47°C) and pre-stretched curd pH (5.1 and 4.9). The qualities of buffalo farm milk met the buffalo milk standards (TAS 6007-2021). A 10 kg pasteurized milk was inoculated with lactic acid bacteria at 40ºC and 0.1 g rennet was added after achieving 0.1 pH decrease in milk. Inoculation starter culture and rennet enzyme caused the pH to drop and milk coagulum to occur. The pH of cultured milk decreased with increasing hardness of milk curd after renneting. At 60 min after renneting the milk curd was suitable for cutting. Low cooking temperature (43°C) prevented cheese curds to coalesce. On the other hand, cooking the cheese curds at a higher temperature (47°C) promoted hardening of the cheese curds. While cooking temperature at 45°C the cheese curds were soft, agglomerated with good stretchability. Chemical compositions of cheese from pre-stretched curd pH 5.1 or 4.9 was similar. Textural quality in terms of hardness and chewiness of pre-stretched curd pH 5.1 were better than that of pH 4.9. The pre-stretched curd pH 5.1 had a better stretchability quality compared to pH 4.9. Recommended manufacturing conditions for mozzarella farm cheese were 60-min curd cutting time, 45°C cooking temperature and pre-stretched curd pH 5.1, respectively